Andean Rhapsody: Notes of a Cosmopolitan Listener (Revista Argentina de Musicología, 2024)
This text aims to explore cosmopolitan representations present in ‘Andean music’, a galaxy of different musical scenes characterised by aspects of transnationality and transculturality. Its intense dialectic between the global and the local makes Andean music fertile ground for cosmopolitan readings. The author imagines a European listener on his journey through the various kinds of Andean music that flourished in his environment from the 1960s onwards. In doing so, he outlines both the dynamics inherent in this listening, often marked by exoticism, and critical interpretations of the phenomenon by popular music scholars and ethnomusicologists. Furthermore, he notes that cosmopolitan perspectives also operate from within the Andean musical space, as expressions of local socio-cultural instances. Finally, he relates the concept of Andean musical cosmopolitanism to the interpretative conflicts surrounding the ‘modernisation’ of folklore and tradition.
Keywords: cosmopolitinaism; transculturality; Andean music; modernization of folklore; musical migrations